Refugia, but Not for Everyone: Genetic Structure Differentiates Shallow and Mesophotic Populations of the Brooder Sponge Ircinia variabilis - Tom Morav; Micha Ilan; Liron Goren; Tal Idan; Sigal Shefer; Yaron Tikochinski; Julio A. Díaz; Giorgos Chatzigeorgiou; Carlota Gracia‐Sancha; Ana Riesgo; Sergi Taboada (Molecular Ecology, 2026)
Understanding how gene‐flow and selection interact across environmental gradients is essential for assessing population resilience and evaluating the deep‐refugia potential of mesophotic habitats under rapid climate change. In the context of depth, genetic connectivity patterns have been documented for broadcast‐spawning species, but that of brooding marine invertebrates remains largely unexplored, leaving the role of mesophotic habitats as potential refugia uncertain. Here, we investigated the genetic structure of the brooder sponge Ircinia variabilis across shallow and mesophotic habitats in the Eastern Mediterranean and across shallow sites spanning multiple Mediterranean basins (i.e., Mallorca, Ionian‐Sea and Israel). By quantifying depth and distance‐related connectivity, and assessing the relative roles of neutral processes and temperature‐driven selection, we evaluated the genetic connectivity of I. variabilis and the potential of mesophotic habitats to function as refugia. Using ddRADseq, we obtained 957 SNPs, to characterize gene‐flow patterns, genetic structure, and environmental influences on differentiation. Ircinia variabilis exhibited pronounced vertical and geographic genetic structure, consistent with limited larval dispersal. Notably, Ionian‐Sea populations were genetically closer to Mallorca than to the geographically closer Israeli populations, suggesting influence of oceanographic barriers. Analyses of selection‐associated loci indicate that environmental variability contributes to population divergence, supporting local adaptation. Along the Israeli coast, pronounced differentiation between shallow and mesophotic populations highlights depth as a key axis of evolutionary divergence. Limited vertical connectivity challenges a central assumption of the deep refugia hypothesis, suggesting mesophotic populations may not sustain shallow populations under climate change.

The spread of Aoroides longimerus Ren & Zheng, 1996 across the Mediterranean and the Atlantic: genetic diversity, anthropogenic transport, and ecological implications - JOSÉ MANUEL GUERRA-GARCÍA; ANDREA DESIDERATO; SERENA MUCCIOLO; CARLOS NAVARRO-BARRANCO; MACARENA ROS; JASMINE FERRARIO; PAULA MORETTI; AGNESE MARCHINI; NAWFEL MOSBAHI; SOFÍA RUIZ-VELASCO; IGNACIO GESTOSO; PATRÍCIO RAMALHOSA; et al. (Mediterranean Marine Science, 2025)
Accurate knowledge of the global distribution of non-indigenous species (NIS) is essential for understanding their invasion dynamics and for implementing timely management measures. This study reports the first records of the marine amphipod Aoroides longimerus, putatively native to the East Asian coast, in Italy (2018), Spain (2019) and Tunisia (2022) and provides the earliest documented record of the species in its introduced European range (Portugal, 2011). Furthermore, it expands the species’ known distribution in mainland Portugal (including the northernmost record), Macaronesia (with first records in the Canary Islands and Madeira), and confirms its presence along the Atlantic coasts of France and the Netherlands. Aquaculture facilities, particularly those associated with oyster farming, are probably the primary vector of introduction, while recreational boating may have contributed significantly to secondary dispersal. In comparison to other exotic amphipods, A. longimerus remains absent from many marinas, ports and/or aquaculture facilities in the Mediterranean Sea and adjacent regions, such as the Red Sea. This suggests that the species may still be in the early stages of expansion, or that its dispersal ability across marinas and ports is more limited than that of other amphipods. The present study, however, highlights several key ecological traits of A. longimerus: (i) it can survive year-round despite seasonal fluctuations, and reach high local densities, (ii) it exhibits strong colonisation capacity, as shown by its rapid establishment on settlement plates, and (iii) it displays opportunistic feeding behaviour, primarily consuming detritus. These characteristics underscore the importance of continuous surveillance and effective communication with stakeholders to prevent further expansion of this species.

Early Succession Patterns of Benthic Assemblages on Artificial Reefs in the Oligotrophic Eastern Mediterranean Basin - Ioannis Rallis; Giorgos Chatzigeorgiou; Marta Florido; Francisco Sedano; Avgi Procopiou; Melina Chertz-Bynichaki; Emmanouela Vernadou; Wanda Plaiti; Panayota Koulouri; Costas Dounas; Vasilis Gerovasileiou; Thanos Dailianis (Journal of Marine Science and Engineering, 2022)
The colonization of artificial structures by benthic organisms in the marine realm is known to be affected by the general trophic patterns of the biogeographical zone and the prevailing environmental traits at the local scale. The present work aims to present quantitative data on the early settlement progress of macrofaunal benthic assemblages developing on artificial reefs (ARs) deployed at the Underwater Biotechnological Park of Crete (UBPC) in the oligotrophic Eastern Mediterranean. Visual census and subsequent image analysis combined with scraped quadrats were used to describe the establishment of the communities and their development over three consecutive campaigns, spanning 5 years post-deployment. Macroalgae consistently dominated in terms of coverage, while sessile invertebrates displayed different patterns over the years. Polychaeta and Bryozoa were gradually replaced by Cnidaria, while Porifera and Mollusca displayed an increasing trend over the years. Motile benthos was mainly represented by Mollusca, while the abundance of Polychaeta increased in contrast to that of Crustacea. For both sessile and motile assemblages, significant differences were observed among the years. The results of this study indicate that ecological succession is still ongoing, and further improvement in the monitoring methodology can assist towards a more accurate assessment of the community composition in complex AR structures.

Ecological patterns of polychaete assemblages associated with the Mediterranean stony coral Cladocora caespitosa (Linnaeus, 1767): a comparison of sites in two biogeographic zones (Adriatic and Aegean Sea) - VALENTINA PITACCO; GIORGOS CHATZIGEORGIOU; BARBARA MIKAC; LOVRENC LIPEJ (Mediterranean Marine Science, 2021)
The Mediterranean stony coral Cladocora caespitosa (Linnaeus, 1767) is a well-known habitat builder, and as such hosts a diversified faunal assemblage. Although polychaetes are one of the most abundant and diverse macrobenthic groups associated with C. caespitosa colonies, our knowledge of their ecological features in this association is still limited. The aim of this paper was to gather and compare the most comprehensive data available on polychaetes associated with C. caespitosa in the Adriatic and the Aegean Seas, and to test for differences between these geographic areas. To this end, differences were tested in terms of: (i) richness and structure of polychaete assemblages; (ii) feeding and functional traits of assemblages; (iii) the main factors influencing those aspects, (iv) the relationship between polychaete assemblages richness and Cladocora colony size, and estimate richness. Differences were observed between the Adriatic and the Aegean Seas, in terms of richness, species composition and relative proportion of the dominant feeding guild (filter feeders most abundant in the Aegean and carnivores in the Adriatic) and motility mode (sessile most abundant in the Aegean and motile in the Adriatic). Conversely, cosmopolitan and Atlanto-Mediterranean species dominated the assemblages in both geographic areas, and the same Species-Area Relation model proved to be effective for richness estimation in both geographic areas.

A Marine Biodiversity Observation Network for Genetic Monitoring of Hard-Bottom Communities (ARMS-MBON) - Matthias Obst; Katrina Exter; A. Louise Allcock; Christos Arvanitidis; Alizz Axberg; Maria Bustamante; Ibon Cancio; Diego Carreira-Flores; Eva Chatzinikolaou; Giorgos Chatzigeorgiou; Nathan Chrismas; Melody S. Clark; et al. (Frontiers in Marine Science, 2020)
Marine hard-bottom communities are undergoing severe change under the influence of multiple drivers, notably climate change, extraction of natural resources, pollution and eutrophication, habitat degradation, and invasive species. Monitoring marine biodiversity in such habitats is, however, challenging as it typically involves expensive, non-standardized, and often destructive sampling methods that limit its scalability. Differences in monitoring approaches furthermore hinders inter-comparison among monitoring programs. Here, we announce a Marine Biodiversity Observation Network (MBON) consisting of Autonomous Reef Monitoring Structures (ARMS) with the aim to assess the status and changes in benthic fauna with genomic-based methods, notably DNA metabarcoding, in combination with image-based identifications. This article presents the results of a 30-month pilot phase in which we established an operational and geographically expansive ARMS-MBON. The network currently consists of 20 observatories distributed across European coastal waters and the polar regions, in which 134 ARMS have been deployed to date. Sampling takes place annually, either as short-term deployments during the summer or as long-term deployments starting in spring. The pilot phase was used to establish a common set of standards for field sampling, genetic analysis, data management, and legal compliance, which are presented here. We also tested the potential of ARMS for combining genetic and image-based identification methods in comparative studies of benthic diversity, as well as for detecting non-indigenous species. Results show that ARMS are suitable for monitoring hard-bottom environments as they provide genetic data that can be continuously enriched, re-analyzed, and integrated with conventional data to document benthic community composition and detect non-indigenous species. Finally, we provide guidelines to expand the network and present a sustainability plan as part of the European Marine Biological Resource Centre ( www.embrc.eu ).

Testing the robustness of a coastal biodiversity data protocol in the Mediterranean: insights from the molluskan assemblages from the sublittoral macroalgae communities - Dimitris Poursanidis; Giorgos Chatzigeorgiou; Charalampos Dimitriadis; Drosos Koutsoubas; Christos Arvanitidis (Hydrobiologia, 2019)

Community structure and population genetics of Eastern Mediterranean polychaetes - Giorgos Chatzigeorgiou; Elena Sarropoulou; Katerina Vasileiadou; Christina Brown; Sarah Faulwetter; Giorgos Kotoulas; Christos D. Arvanitidis (Frontiers in Marine Science, 2014)